THE EFFECT OF METEOROLOGICAL CONDITIONS ON THE FORMATION OF PEAS PRODUCTIVITY - F. A. Davletov; K. P. Gaynullina; I. K. Karimov (Зерновое хозяйство России, 2018)
The article is devoted to the study of changeability of the length of vegetation and interphase periods of peas (Pisum sativum L.) in the Pre-Ural Steppe of Bashkortostan. The article gives the comparison of the vegetation and interphase periods with separate meteorological factors and seed productivity through the coefficients of variation (V). Peas is the main leguminous crop in Bashkortostan. The length of vegetation and interphase periods of peas is determined through the varietal features and their interconnections with the environmental conditions. A detailed study of these periods for different varieties in the definite conditions is of great scientific and practical interest for the plant-breeding. The climate of theRepublicofBashkortostanis continental with long cold winter and hot dry summer.  The agro meteorological conditions during the periods of peas growth and development in 1999-2013 were largely contrasting, which allowed assessing the effect of unfavourable environmental conditions on the length of vegetation and interphase periods of peas. In our experiments the length of the period ‘seeding-sprouting’ largely depended on average daily temperature of air (r=-0.875). The length of the period ‘sprouting-flowering’, except the varietal peculiarities, depended on the temperature regime (r= -0.874 – -0.886). The precipitations increased the length of the period of ‘sprouting- flowering’ (r=0.626 – 0.668). Both precipitations and temperature influenced a lot on the length of the period of ‘seeding-maturing’ of the peas varieties. The coefficients of the correlation were r=-0.653 – -0.658 and r=0.629 – 0.650 respectively. The seed productivity was positively dependent on the length of the period of ‘seeding- maturing’ with r=0.548. The increase of average daily temperature of air negatively affected on the seed productivity (r=-0.769). The interrelation between the seed productivity and the sum of precipitations and the hydrothermal coefficient turned to be r=0.301 and r=0.290 respectively.